2018
DOI: 10.1088/1742-5468/aae84a
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic heat engine powered by active dissipation

Abstract: Thermodynamics of nanoscale devices is an active area of research. Despite their noisy surrounding they often produce mechanical work (e.g. micro-heat engines), display rectified Brownian motion (e.g. molecular motors). This invokes research in terms of experimentally quantifiable thermodynamic efficiencies. Here, a Brownian particle is driven by a harmonic confinement with time-periodic contraction and expansion. The system produces work by being alternately (time-periodically) connected to baths with differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Recent studies demonstrated that the stochastic efficiency of Brownian heat engines driven by the non-equilibrium protocol is not bounded and can even exceed Carnot efficiency [51][52][53][54][55][56][57][58]. Here, we study the stochastic efficiency η; À βW=I of the information engine owing to the fluctuations in work and mutual information (Figure 3).…”
Section: Efficiency Fluctuationsmentioning
confidence: 99%
“…Recent studies demonstrated that the stochastic efficiency of Brownian heat engines driven by the non-equilibrium protocol is not bounded and can even exceed Carnot efficiency [51][52][53][54][55][56][57][58]. Here, we study the stochastic efficiency η; À βW=I of the information engine owing to the fluctuations in work and mutual information (Figure 3).…”
Section: Efficiency Fluctuationsmentioning
confidence: 99%
“…(15) at a given time point t is negligibly small. Quasistatic limit in similar systems was also explored to calculate relevant thermodynamic quantities analytically in [15,30,31]. We note that in the second half of the cycle it is not possible to define an effective temperature T ef f since the heat bath is out of equilibrium.…”
Section: General Casementioning
confidence: 99%
“…While calculating the thermodynamic quantities such as work and heat in quasistatic limit, we will use respective cases in Eq. (15). For instance, the average energy of the trapped particle is given by U = 1 2 kσ x .…”
Section: General Casementioning
confidence: 99%
See 2 more Smart Citations